Analisis Perbandingan Harga Pokok Produksi Menggunakan Metode Job Order Costing dan Metode Activity Based Costing di UD. Cirasa - Azis Syarif, Abdul; Jhon Frans Simanjuntak , Edo; Novalia Harahap, Uun; Zaharuddin , Zaharuddin (SURYA TEKNIKA, 2026)
This study aims to analyze and compare the calculation of cost of goods manufactured (COGM) at UD. Cirasa using traditional methods, Job Order Costing, and Activity Based Costing (ABC). The research employs a comparative approach with data collected through observation and interviews. The results show that the traditional method produces a unit cost of Rp 1,777, the ABC method Rp 1,577, and the Job Order Costing method Rp 1,826. These differences arise from the way overhead costs are allocated in each method. The ABC method provides more accurate results because it assigns costs based on production activities. Therefore, ABC is considered more effective in determining production costs and can be used as a reliable basis for setting appropriate selling prices.